Prospects of the development of ukrainian society through the prism of L. Kuchma’s work “Ukraine is not Russia” - Chornyi , Vitalii (Social Development and Security, 2021)
The article analyzes the development of a number of newly independent states, namely South Korea, Indonesia, the Philippines and Taiwan, which, according to the second President of Ukraine Leonid Kuchma, in a short period of time achieved impressive results due to successful modernization. It is established that the main conditions for the success of these countries are laid down in the universal formula “strong state, social order, discipline”. This formula provided for a program of action, namely: the centralization of power in the hands of a strong president as the only means of consolidating society; priority of economic modernization; liquidation of the clan-oligarchic system; carrying out effective agrarian reform. Based on the above, the doctrinal principles on which the modern Ukrainian state should be based are substantiated. These principles are aimed at forming a community of wealthy, self-sufficient citizens with a developed sense of dignity and optimism, which, in turn, is a code for a reset and a new way of creating a Greater Ukraine.